AKTIVISME GERAKAN KEAGAMAAN DALAM KONTEKS KEBUDAYAAN : Antara Penegakan Syariat dan Anomali - Fuat Edi Kurniawan; Defbry Margiansyah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
This academic work discusses about an activism of the religious movement recently emerging as a response against Liberal Islam in Indonesia. The rise of such movement is interesting to be studied in order to search a deeper understanding on the relationship between expression of religious piety and culture in the context of Indonesia. This article focuses on the case of the enforcement to shut down a transgender Islamic school (Pesantren Waria) and the rejection of Easter celebration conducted by Religious forum in Yogyakarta. The analysis of the article’s identified problems are explained into three forms of conclusion; First, the phenomenon of religious movement activism is understood as a counter culture through which they set a standard of conduct derived from their own conception of truth. Second, there is construction of collective religious identity integrated with ethnic identity. Third, such religious identity construct is increasingly established as moral legitimacy in existing social order. As consequence, the movement perceives that the society no longer needs a set of values derived from external circumstances such as egalitarianism, humanity, gender justice, and others.Artikel ini membahas aktivisme gerakan keagamaan kontemporer yang akhir-akhir ini muncul sebagai respon balik terhadap Islam liberal di Indonesia. Kemunculan gerakan keagamaan ini menarik untuk dikaji sebagai pemahaman mengenai hubungan ekspresi kesalehan umat beragama dan konteks kebudayaan di Indonesia. Dalam artikel ini mengambil kasus di Yogyakarta yang dilakukan oleh forum keagamaan yang melakukan penutupan paksa pesantren waria dan penolakan acara paskah. Ketidaksesuaian produk kebudayaan dengan nilai-nilai agama dominan (Islam) menjadi alasan utama gerakan keagamaan yang cenderung radikal ini untuk melakukan tindakan-tindakan penolakan. Artikel ini mengidentifikasi setidaknya kedalam tiga kesimpulan; Pertama, fenomena aktivisme gerakan keagamaan dipahami sebagai deviant subculture, mereka menentukan standar berperilaku yang diyakini mereka sebagai kebenaran. Kedua, terbentuknya identitas kolektif keagamaan yang terintegrasi dengan identitas etnik. Ketiga, semakin kuatnya legitimasi moral dalam tatanan sosial. Mereka merasa tidak memerlukan lagi perangkat nilai lain yang datang dari luar, seperti nilai egaliter, kemanusiaan, dan keadilan.